Exploring expanded interdisciplinary roles in goals of care conversations in a national goals of care initiative: A qualitative approach. (September 2021) - Ma, Jessica E; Haverfield, Marie; Lorenz, Karl A; Bekelman, David B; Brown-Johnson, Cati; Lo, Natalie; Foglia, Mary Beth; Lowery, Jill S; Walling, Anne M; Giannitrapani, Karleen F
Background: The United States Veterans Health Administration National Center for Ethics in Health Care implemented the Life-Sustaining Treatment Decisions Initiative throughout the Veterans Health Administration health care system in 2017. This policy encourages goals of care conversations, referring to conversations about patient's treatment and end-of-life wishes for life-sustaining treatments, among Veterans with serious illnesses. A key component of the initiative is expanding interdisciplinary provider roles in having goals of care conversations. Aim: Use organizational role theory to explore medical center experiences with expanding interdisciplinary roles in the implementation of a goals of care initiative. Design: A qualitative thematic analysis of semi-structured interviews. Setting/participants: Initial participants were recruited using purposive sampling of local medical center champions. Snowball sampling identified additional participants. Participants included thirty-one interdisciplinary providers from 12 geographically diverse initiative pilot and spread medical centers. Results: Five themes were identified. Expanding provider roles in goals of care conversations (1) involves organizational culture change; (2) is influenced by medical center leadership; (3) is supported by provider role readiness; (4) benefits from cross-disciplinary role agreement; and (5) can "overwhelm" providers. Conclusions: Organizational role theory is a helpful framework for exploring interdisciplinary roles in a goals of care initiative. Support and recognition of provider role expansion in goals of care conversations was important for the adoption of a goals of care initiative. Actionable strategies, including multi-level leadership support and the use of interdisciplinary champions, facilitate role change and have potential to strengthen uptake of a goals of care initiative.